Comparison of hyperpolarized 3He-MRI, CT based parametric response mapping, and mucus scores in asthmatics - Carey, Katherine J.; Hotvedt, Peter; Mummy, David G.; Lee, Kristine E.; Denlinger, Loren C.; Schiebler, Mark L.; Sorkness, Ronald L.; Jarjour, Nizar N.; Hatt, Charles R.; Galban, Craig J.; Fain, Sean B. (Frontiers in Physiology, 2023)
The purpose of this study was to anatomically correlate ventilation defects with regions of air trapping by whole lung, lung lobe, and airway segment in the context of airway mucus plugging in asthma. A total of 34 asthmatics (13M:21F, 13 mild/moderate, median age [range] of 49.5 [36.8 – 53.3] years and 21 severe, 56.1 [47.1 – 62.6] years) and 4 healthy subjects (1M:3F, 38.5 [26.6 – 52.2] years) underwent HP 3He MRI and CT imaging. HP 3He MRI was assessed for ventilation defects. Inspiratory and expiratory CTs were analyzed using parametric response mapping (PRM) to quantify markers of emphysema and functional small airways disease (fSAD). Segmental and lobar lung masks were obtained from CT and registered to HP 3He MRI in order to localize ventilation defect percentage (VDP), at the lobar and segmental level, to regions of fSAD and mucus plugging. Biomarkers were correlated with PFT's and each other on a global and lobar level, and a multivariate analysis was conducted to predict segmental fSAD given segmental VDP (sVDP) and mucus score as variables. The fSAD was correlated with whole lung VDP (r = 0.65, p<0.001), mucus score (r=0.55, p<0.01), and moderately correlated (-0.60 ≤ r ≤ -0.56, p<0.001) to percent predicted (%p) FEV1, FEF25-75 and FEV1/FVC, and more weakly correlated to FVC%p (-0.38 ≤ r ≤ -0.35, p<0.001). Lobar VDP, mucus scores, and fSAD were also moderately correlated (r from 0.45-0.66, p<0.01). For segmental colocalization, the model of best fit was a piecewise quadratic model, which suggests that sVDP may be increasing due to local airway obstruction that doesn’t manifest as fSAD until more extensive disease is present. sVDP was more sensitive to the presence of a mucus plugs overall, but the prediction of fSAD using multivariate regression showed an interaction in the presence of a mucus plugs when sVDP was between 4-10% (p<0.001). This multi-modality study in asthma confirmed that areas of ventilation defects are spatially correlated with air trapping at the level of the airway segment and suggests VDP and fSAD are sensitive to specific sources of airway obstruction in asthma, including mucus plugs.